Indeks Pembangunan Manusia dan Pendidikan di Jawa Tengah - Mohammad Fauzan; Agung Nusantara; Sri Nawatmi; Agus Budi Santosa (Jurnal Bisnis dan Ekonomi, 2020)
The Human Development Index (HDI) is an internationally recognized measure of importance to describe the success of human development. Therefore, the development of HDI needs to get an important spotlight in determining development policy. One important dimension of HDI is education, as measured by Expected Years of Schooling (EYS) and Mean Years of Schooling (MYS). The EYS figure illustrates people's expectations for continuing education by basing themselves on government-made education policies. While MYS describes the reality of the old school that can be enjoyed by the community. Central Java indicates that the EYS is larger than the MYS but with a narrowing distance. This fact illustrates that education policy in Central Java is increasingly accessible to the public. However, nationally the level of education in Central Java is still low. Some factors that cause is still high dropout rate at age 16-18 year